Antimicrobial Activity of Methanolic Extracts of Bamboo Shoots Bambusa vulgaris - Naidu, M A (International Journal of Pharmaceutical & Biological Archive, 2013)
Antimicrobial Activity of Methanolic Extracts of Bamboo Shoots Bambusa vulgaris